WO3-loaded TIO2 nanotubes via electrochemical anodization technique for efficient photocatalytic removal of mercury / Lee Wai Hong - Lee, Wai Hong (2016)

(untitled)
Mercury removal from both air emissions and industrial wastewater are key targets for the environmental sustainability strategy to ensure a healthy environment for future generation. The formation of self-organized titanium dioxide (TiO2) nanotubes without bundling is essential for high efficiency in mercury removal. Thus, this research aims to study on the development of an efficient WO3-loaded TiO2 nanotubes catalyst for the removal of mercury ions. WO3-loaded TiO2 nanotubes were synthesized through single step electrochemical anodization technique by using tungsten as the cathodic material instead of the conventionally used platinum electrode. As compared with platinum, tungsten (W) metal has lower chemical stability, forming dissolved ions (W6+) in the electrolyte. The W6+ ions then moved towards the titanium foil and formed a coherent deposit on titanium foil. In fact, coupling TiO2 with W6+ species will lead to an additional electronic state in the band-gap, which in turn affect a change in the electronic and functionality of TiO2 itself. Comprehensive investigations on different parameters, such as composition of electrolyte, anodization time, and anodization voltage were conducted in order to control the specific architecture of nanotubes. Highly ordered WO3-loaded TiO2 nanotube films (0.22 to 3.29 at% of W) were successfully synthesized through anodization of titanium (Ti) foil in ethylene glycol containing ammonium fluoride (NH4F). It was found that this resultant WO3-loaded TiO2 nanotubes demonstrated a maximum mercury removal rate of 91% in 120 minutes. This performance was approximately 1.4 times higher than the pure TiO2 nanotubes. The presence of W element in TiO2 showed an improvement of mercury removal efficiency because it acted as an effective mediator to trap the photo-induced electrons and minimize the recombination of charge carriers.